High stromal Foxp3-positive T cell number combined to tumor stage improved prognosis in head and neck squamous cell carcinoma. (April 2017) - Kindt, Nadège; Descamps, Géraldine; Seminerio, Imelda; Bellier, Justine; Lechien, Jérôme R.; Mat, Quentin; Pottier, Charles; Delvenne, Philippe; Journé, Fabrice; Saussez, Sven
Highlights: Foxp3-positive T cell numbers increase during HNSCC progression. Stromal Foxp3 T cell numbers predict recurrence and survival in HNSCC patients. Foxp3 T cell numbers combined to tumor stage improve prognostic of HNSCC patients. Foxp3-positive T cell numbers increase in HPV-positive patients. E7 oncoprotein increase the Foxp3 T cells infiltration in the tumors in mice. Abstract: Objectives: Head and neck squamous cell carcinomas (HNSCC), one of the most frequent cancers in the world, are largely infiltrated by inflammatory immune cells. Our aim was to evaluate the number of Foxp3+ T cells in HNSCC, reporting its prognostic power in comparison to other risk factors. Material and methods: Our clinical series was composed of 21 tumor-free peri-tumoral epithelia, 49 low grade dysplasia, 43 high grade dysplasia and 110 carcinoma samples including some cases with HPV infection. In vivo experiments were conducted on 80 C3 H/HeN mice which were orthotopically injected with SCCVII CT, E7, E6 and E6/E7 cell lines. Results: Foxp3+ T cell infiltration increased with tumor progression from normal epithelia, dysplasia to carcinoma and the increase is more important in HPV+ patients than in negative ones. Animal experiments revealed that E7 oncoprotein expression was significantly associated with an increase in Foxp3+ T cell recruitment in tumor, a delay in tumor onset and improved animal survival. Univariate Cox regression analyses demonstrated that high Foxp3+ T cell number in stromal compartment is associated with longer patient recurrence-free and overall survivals. Foxp3+ T cell number improved the prognostic value of tumor stage. Multivariate analyses reported that stromal Foxp3+ T cell number is a strong prognostic factor independent of classical risk factors such as tobacco, alcohol, and HPV status. Conclusion: Foxp3+ T cell number is a significant prognostic factor for HNSCC, improving the tumor stage, and that viral E7 may play a role in the Foxp3+ T cell infiltration to the tumor.